2011
DOI: 10.1093/molbev/msr161
|View full text |Cite
|
Sign up to set email alerts
|

Unity in Variety--The Pan-Genome of the Chlamydiae

Abstract: Chlamydiae are evolutionarily well-separated bacteria that live exclusively within eukaryotic host cells. They include important human pathogens such as Chlamydia trachomatis as well as symbionts of protozoa. As these bacteria are experimentally challenging and genetically intractable, our knowledge about them is still limited. In this study, we obtained the genome sequences of Simkania negevensis Z, Waddlia chondrophila 2032/99, and Parachlamydia acanthamoebae UV-7. This enabled us to perform the first compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
299
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(322 citation statements)
references
References 117 publications
19
299
1
Order By: Relevance
“…amoebophila genome has a genomic island (Pam100G) that encodes a type IV secretion system of the F-type that might be involved in conjugative DNA transfer (Greub et al 2004). A similar system is also found on the plasmid of Simkania negevensis (Collingro et al 2011) and a partial operon was described in Parachlamydia acanthamoebae ), suggesting active DNA transfer capabilities in the ancestor of the Chlamydiales and some of its descendants.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…amoebophila genome has a genomic island (Pam100G) that encodes a type IV secretion system of the F-type that might be involved in conjugative DNA transfer (Greub et al 2004). A similar system is also found on the plasmid of Simkania negevensis (Collingro et al 2011) and a partial operon was described in Parachlamydia acanthamoebae ), suggesting active DNA transfer capabilities in the ancestor of the Chlamydiales and some of its descendants.…”
Section: Introductionsupporting
confidence: 52%
“…amoebophila UWE25 chromosome (Greub et al 2004), the plasmids of S. negevensis (Collingro et al 2011) and Rubidus massiliensis, and the remnants traU, traN and traF present in members of the family Parachlamydiaceae Collingro et al 2011) (fig. 3).…”
Section: Chromosome Featuresmentioning
confidence: 99%
“…(SI Appendix, Table S5). A recent study reported that an obligate endosymbiont, Candidatus Ameobophilus asiaticus, of a free-living amoeba, also lacking almost all amino acid biosynthesis pathways, contains a large fraction of proteins with eukaryotic domains (67,68). It was demonstrated that these domains are also significantly enriched in the genomes of other amoeba-associated bacteria (including Legionella pneumophilia, Ricksettsia bellii, Francisella tularensis, and M. avium).…”
Section: Discussionmentioning
confidence: 99%
“…Chlamydia genomes have undergone a large degree of reductive evolution, Chlamydiaceae more so than environmental Chlamydiales given the 2-3 times smaller genomes found within that order (62). The environmental Chlamydiales are significantly more metabolically flexible than Chlamydiaceae, encoding additional genes involved in sugar utilization, a complete TCA cycle, and an expanded electron transport chain, among other pathways (61).…”
Section: Discussionmentioning
confidence: 99%